Faktor-Faktor yang Dominan Mempengaruhi Permintaan Pada Aplikasi Belanja Online - Ni Made Rianita Nova Damayanthi; Ni Putu Rediatni Giri; Anak Agung Ketut Jayawarsa (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2023)
This study is meaningful to analyze the factors that have a demand on online shopping applications. This study uses the Slovin formula with 100 people. The analysis technique in this study is an exploratory factor. Where the results of this study show that the dominant factor influencing the demand for Online Shopping Applications in Denpasar City as a whole is outlined in factor 1, which is dominant, namely taste and then forecasting future conditions. Judging from the results of the study, there is 1 factor that influences the demand for Online Shopping Applications in Denpasar City, namely the taste factor and forecasting conditions in the future.